Analisis Penerapan Manajemen Resiko Kredit Dalam Meminimalisir Kredit Bermasalah Pada Bank Lampung (Studi kasus pada PT. Bank Lampung KC Bandar Lampung) - Edo Then; Defrizal Defrizal (Universitas 17 Agustus 1945, 2023)
This research has two purpose. First purpose to identify any kind of risk that appeared from bank activity on PT. Bank Lampung KC Bandar Lampung. Second purpose to know appliance of risk management for minimizing Non Performing Loan– NPL on one of their product, Kredit of Bank Lampung. The result of identifying the risk show that the risk which appeared from bank activity PT. Bank Lampung KC Bandar Lampung are credit risk, operational risk, and reputation risk. Credit risk are focus of this research. Risk credit appear on the form No Performing Loan that caused by several factor, that is internal, external, and other factor. To minimiz ecredit risk, PT. Bank Lampung KC Bandar Lampung has applying good risk management and provesuccesfully minimizing Non Performing Loan. The success of PT. Bank Lampung KC Bandar Lampung can be proven from NPL ratio that not exceed Bank Indonesia’s regulation no more than 5% and Bank Lampung Central Office’sregulation, no morethan 3%.